2014
DOI: 10.1111/aas.12420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pregabalin for treating painful diabetic peripheral neuropathy: a meta‐analysis

Abstract: Our meta-analysis indicates that pregabalin is more effective than placebo for managing DPN-associated pain and other symptoms that reduce quality of life. The drug is also reasonably well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Regarding specific conditions, the Cochrane Collaboration [48]. Pregabalin was found to be efficacious compared with placebo in improving pain scores (mean difference -0.79) and in the proportion of patients achieving a reduction of ≥50% in pain intensity (RR 1.54) in patients with painful diabetic peripheral neuropathy [73]. Gabapentin and pregabalin have not been shown to be effective in ameliorating pain in patients with HIV-associated neuropathy [74].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Regarding specific conditions, the Cochrane Collaboration [48]. Pregabalin was found to be efficacious compared with placebo in improving pain scores (mean difference -0.79) and in the proportion of patients achieving a reduction of ≥50% in pain intensity (RR 1.54) in patients with painful diabetic peripheral neuropathy [73]. Gabapentin and pregabalin have not been shown to be effective in ameliorating pain in patients with HIV-associated neuropathy [74].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…23 In clinical trials of patients with peripheral neuropathic pain, gabapentinoids have consistently demonstrated significant benefit. 24-26 However, only a minority of patients achieved substantial pain relief, with many not responding. Patients with CIBP generally have multiple serious morbidities and a more complex array of factors contributing to their hypersensitivity, as a result of immunologic responses to the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of pregabalin for pDPN treatment have been established in multiple studies conducted in the US, Europe, Japan, and Korea . A recently concluded pooled analysis of 2056 patients further confirmed the efficacy of pregabalin for pDPN treatment . In China, pregabalin is approved for PHN treatment .…”
Section: Introductionmentioning
confidence: 92%